Comparison of Legal Systems in Land Acquisition for Public Interest in Indonesia, Malaysia, China, and the United States - Sahne Fa Alhama Ibrahim Sakti; Handar Subhandi Bakhtiar (Journal of Ius Comparatum Law Studies, 2026)
Land acquisition for the public interest is an important aspect of a country's development, with different policies in eachcountry according to the legal system and socio-political factors. This study compares the legal systems governing landacquisition in Indonesia, Malaysia, China, and the United States, focusing on procurement, compensation, and dispute-resolution mechanisms. The method used is a normative legal approach with qualitative analysis of secondary data fromregulations, journals, and literature. The results show that Indonesia and Malaysia rely on deliberation, but still facechallenges in fair compensation. China prioritises state control over land, often overriding individual rights, whereas theUnited States applies eminent domain with stronger legal protections for landowners. Each country has advantages anddisadvantages in balancing development interests and the rights of landowners. Indonesia needs to increase transparencyin land price valuations and strengthen legal access for landowners. The adoption of best practices from other countries,such as market-value-based compensation systems and clearer government authority, can help achieve fairer and moreeffective land acquisition policies.